The Effects of Bacillus licheniformis on the Growth, Biofilm, Motility and Quorum Sensing of Salmonella typhimurium - Wenwen Peng; Haocheng Xu; Meiting Zhang; Baoyang Xu; Bing Dai; Caimei Yang (Microorganisms, 2025)
With 80% of bacterial infections occurring as biofilms, biofilm-related infections have evolved into a critical public health concern. Probiotics such as Bacillus licheniformis have emerged as promising alternatives, offering new avenues for effective treatment. This study aimed to evaluate the activity of licheniformis against the growth, biofilm formation, motility, and quorum sensing (QS) of Salmonella typhimurium. Several experiments were conducted: The minimum inhibitory concentration (MIC) of Bacillus licheniformis against Salmonella typhimurium was determined to be 0.5 mg/mL using the broth microdilution method. The inhibition zone of 100 mg/mL of B. licheniformis against Salmonella typhimurium was 19.98 ± 1.38 mm; the time-growth curve showed that B. licheniformis can effectively inhibit the growth of Salmonella typhimurium. In biofilm experiments, at the MIC of B. licheniformis, the inhibition rate of immature biofilm of Salmonella typhimurium was 86.9%, and it significantly reduced the production of biofilm components (EPS, e-DNA, and extracellular proteases) (p < 0.05). The disruption rate of mature biofilm by B. licheniformis at the MIC was 66.89%, and it significantly decreased the levels of biofilm components (EPS and e-DNA) (p < 0.5). Microscopic observation showed that both the MIC and 1/2 MIC of B. licheniformis could reduce the number of bacteria in the Salmonella typhimurium biofilm, which was not conducive to the formation and maintenance of the biofilm structure. Swimming/Swarming assays and QS experiments confirmed that B. licheniformis inhibits the motility of Salmonella typhimurium and the secretion of AI-1-type quorum sensing molecules and downregulates the AI-2 quorum sensing system by upregulating lsr gene expression. These findings suggest that B. licheniformis could be a potential antimicrobial agent and biofilm inhibitor.